Human rights and the end of empire : the British role in the genesis - Simpson, Brian (Oxford : Oxford University Press, 2004)
The European Convention on Human Rights of 1950 established the most effective international system of human rights protection which has yet been invented. This is the first book that gives a comprehensive account of how it came into existence.
Includes bibliographical references and index.
Keywords: European Convention on Human Rights -- (1950); Human rights -- Great Britain; Droits de l'homme (Droit international) -- Grande-Bretagne.; British colonies; Human rights; Great Britain -- Colonies; Grande-Bretagne -- Colonies; Great Britain